Smallholder farm size distribution across sub-Saharan Africa - Hougni, Deo-Gratias; Silva, Joao Vasco; Chamberlin, Jordan (International Maize and Wheat Improvement Center, 2024)
Farm size is a key asset to smallholder farmers, strongly correlated to other farm resources. Understanding farm size distribution is therefore important to target and scale up interventions whose adoptability is intricately linked to farm resource endowment. Although, heterogeneity in farm sizes is recognised across Sub-Saharan Africa (SSA), there is a longstanding challenge to describe and characterize it. A panel of household surveys run across 14 countries between 2008 and 2021 was used to evaluate the capacity of selected biophysical and socioeconomic features to infer and predict spatial farm size distribution. The features include, but are not limited to population density, long-term annual air temperature and rainfall, travel time to the nearest city. The unit of spatial analysis was a grid cell of about 10 km x 10 km. Using a random-forest model, the complete set of features was able to explain 50% of the variation in average farm sizes across the continent. The relative importance of individual features was country-specific. These results highlight the spatial clustering of average farm sizes, the adequacy of fitting locally farm sizes to log-normal distribution, and the multiplicity of farm size drivers across the continent.